Prospective estimation of duration of pregnancy in women attending antenatal care at the Sultania Zanana Hospital, Gandhi Medical College Bhopal, Madhya Pradesh, India - Goyal, Megha; Wadhwani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Correct assessment of pregnancy duration and fetal growth is essential for optimal obstetric management. The objective of this study was to estimate the accuracy of Naegele’s formula in estimation of gestational age and duration of pregnancy in Sultania Zanana Hospital, Bhopal, Madhya Pradesh, India. Hospital based prospective observational study. Department of obstetrics and gynecology, Sultania Zanana Hospital, Gandhi Medical College, Bhopal, a one year study from April 2014 to March 2015. Methods: This was a prospective observational study of 500 antenatal women selected at random with regular menstrual cycle, which knew their last menstrual period and delivered spontaneously in Sultania Zanana hospital between April 2014 to March 2015. The mean duration of pregnancy was calculated using Naegele`s formula. Results: Most of the patients were in their 2nd decade of life. Most of them were para 2, 3 and 4. The mean duration of pregnancy was 276.04±8 days. Conclusions: The duration of pregnancy 276 days appears more applicable in our environment.